Consensus framework for conducting phase I/II clinical trials for children, adolescents, and young adults with pediatric low-grade glioma: guidelines established by the International Pediatric Low-Grade Glioma Coalition Clinical Trial Working Group - Müller, Sabine; Fangusaro, Jason; Thomas, Arzu Onar; Jacques, Thomas S; Bandopadhayay, Pratiti; de Blank, Peter; Packer, Roger J; Fouladi, Maryam; van Meeteren, Antoinette Schouten; Jones, David T. W.; Perry, Arie; Nakano, Yoshiko; et al. (Neuro-Oncology, 2024)
Within the last few decades, we have witnessed tremendous advancements in the study of pediatric low-grade gliomas (pLGG), leading to a much-improved understanding of their molecular underpinnings. Consequently, we have achieved successful milestones in developing and implementing targeted therapeutic agents for treating these tumors. However, the community continues to face many unknowns when it comes to the most effective clinical implementation of these novel targeted inhibitors or combinations thereof. Questions encompassing optimal dosing strategies, treatment duration, methods for assessing clinical efficacy, and the identification of predictive biomarkers remain unresolved. Here, we offer the consensus of the international pLGG coalition (iPLGGc) clinical trial working group on these important topics and comment on clinical trial design and endpoint rationale. Throughout, we seek to standardize the global approach to early clinical trials (phase I and II) for pLGG, leading to more consistently interpretable results as well as enhancing the pace of novel therapy development and encouraging an increased focus on functional endpoints as well and quality of life for children faced with this disease.